2019
DOI: 10.3389/fonc.2019.01260
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA SNHG12 Functions as a Competing Endogenous RNA to Regulate MDM4 Expression by Sponging miR-129-5p in Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC), the most common histological subtype of kidney cancer, shows poor prognosis, and non-sensitivity to radiotherapy or chemotherapy. The lncRNA small nucleolar RNA host gene 12 (SNHG12) has been revealed to play a carcinogenic role in various neoplasms, but the underlying mechanism in ccRCC is still unclear. To explore the potential role of SNHG12 in ccRCC, the data downloaded from the Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) Data Portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…The open access of microarray and high-throughput sequencing data have allowed increasing number of researchers to use comprehensive bioinformatics such as mRNA ( He et al, 2020 ), miRNA ( Xiao et al, 2020 ), and lncRNA ( Wu et al, 2019 ) to explore the novel signatures related to tumor progression and prognosis of ccRCC patients. However, the small sample size of individual studies and differences in sequencing platforms and lab protocols can render great variability among the studies.…”
Section: Introductionmentioning
confidence: 99%
“…The open access of microarray and high-throughput sequencing data have allowed increasing number of researchers to use comprehensive bioinformatics such as mRNA ( He et al, 2020 ), miRNA ( Xiao et al, 2020 ), and lncRNA ( Wu et al, 2019 ) to explore the novel signatures related to tumor progression and prognosis of ccRCC patients. However, the small sample size of individual studies and differences in sequencing platforms and lab protocols can render great variability among the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, miR-129-5p is considered to be a tumor suppressor and is down-regulated in prostate cancer (PC) 21 , bladder cancer (BC) 22 , etc. Wu Z et al pointed out that the long non-coding RNA SNHG12 acts as a competing endogenous RNA to regulate MDM4 expression by competing with miR-129-5p in ccRCC 12 . In this study, we found that miR-129-5p was signi cantly downregulated in ccRCC by bioinformatics analysis and cell experiments, and it was in agreement with the report of Wu Z et al Besides, overexpression of miR-129-5p was found to suppress ccRCC cell proliferation, migration and invasion by serving as a tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have elucidated that miR-129-5p is considerably differentially expressed and exerts an essential role in colon cancer 8 , liver cancer 9 , pancreatic cancer 10 and gastric cancer, etc 11 . Despite that the regulatory role of miR-129-5p in ccRCC has been studied before 12 , the regulatory mechanism of miR-129-5p in the occurrence and development of ccRCC requires further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…11 The small nucleolar RNA host gene 12 (SNHG12) is located at chromosome 1p35.3 and is involved in multiple cancers, including cervical cancer, renal cell carcinoma, prostate cancer, nasopharyngeal carcinoma, colorectal cancer and hepatocellular carcinoma. [12][13][14][15][16][17] However, SNHG12 biological role and related mechanisms in DLBCL remain unknown.…”
Section: Introductionmentioning
confidence: 99%